2009
DOI: 10.1021/ma9007913
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles with Individual Site-Isolated Semiconducting Polymers from Intramolecular Chain Collapse Processes

Abstract: We present the synthesis of polymeric nanoparticles from single ABA type block copolymers in an intramolecular-chain process to result 3-D architectures that confine a single chain of conducting copolymers. ABA triblock copolymers were prepared from conducting polymers such as fluorene homopolymers and fluorene/thiophene copolymers designed as telechelic macroinitiators to facilitate nitroxide-mediated living free radical polymerization methods. The polymerization with styrene and vinylbenzosulfone cross-linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…I agree with the suggested changes, that can be made easily by the editorial office. [7,22,28,29], poly(styrene) [3,22,23,[30][31][32], poly(haloalkyl styrene) [3,33], poly(4-N-Boc-vinylaniline) [33], poly(sodium 4-styrenesulfonate) [22], poly(N-alkyl acrylamide) [22,34,35] Atom transfer radical polymerization ATRP Poly(alkyl methacrylates) [14], poly(alkyl acrylates) [11,12], poly(styrene) [36], poly(N-hydroxyethyl acrylamide) [37] Nitroxide mediated radical polymerization NMP Poly(alkyl methacrylates) [9,[38][39][40], poly(alkyl acrylates) [40], poly(styrene) [2,38,40], poly(haloalkyl styrene) [40], poly(fluorene) [41] Ring opening metathesis polymerization ROMP Poly(-caprolactone) [38], poly(carbonates) [42] poly(norbornenes) [13,43,44] * For SCNP copolymer and terpolymer precursors, only the nature of the main component is indicated.…”
Section: Controlled Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…I agree with the suggested changes, that can be made easily by the editorial office. [7,22,28,29], poly(styrene) [3,22,23,[30][31][32], poly(haloalkyl styrene) [3,33], poly(4-N-Boc-vinylaniline) [33], poly(sodium 4-styrenesulfonate) [22], poly(N-alkyl acrylamide) [22,34,35] Atom transfer radical polymerization ATRP Poly(alkyl methacrylates) [14], poly(alkyl acrylates) [11,12], poly(styrene) [36], poly(N-hydroxyethyl acrylamide) [37] Nitroxide mediated radical polymerization NMP Poly(alkyl methacrylates) [9,[38][39][40], poly(alkyl acrylates) [40], poly(styrene) [2,38,40], poly(haloalkyl styrene) [40], poly(fluorene) [41] Ring opening metathesis polymerization ROMP Poly(-caprolactone) [38], poly(carbonates) [42] poly(norbornenes) [13,43,44] * For SCNP copolymer and terpolymer precursors, only the nature of the main component is indicated.…”
Section: Controlled Polymerizationmentioning
confidence: 99%
“…Covalent bonding interactions Vinyl [33,38,39,42] Radical coupling & Cross-Metathesis Benzocyclobutene [40,53] Diels-Alder reaction * Benzosulfone [9,28,41] Diels-Alder reaction * Azide + Protected alkyne [3,10,21,22,30,34] Copper-catalyzed [3+2] cycloaddition ** Carboxilic acid [54] Amide formation Isocyanate [23] Urea formation ** Enediyne [11,12,24,29] Bergman & Photo-Bergman cyclization Sulfonyl azide [31] Nitrene-mediated cross-linking Benzoxazine [36] Ring opening polymerization Alkyne [25] Glaser-Hay coupling * * C-C click chemistry. ** N-C click chemistry.…”
Section: Reactive Functional Groupsmentioning
confidence: 99%
“…The Barner-Kowollik group demonstrated a photo-induced Diels-Alder ligation to create SCNP in addition to using metal-ligand complexation to induce controlled folding by linking chain ends [1,24]. Other work has demonstrated that SCNP can be formed from a host of reactions including benzocylcobutene coupling [25], olefin cross-metathesis [26], azide-alkyne click chemistry [19,[27][28][29][30], thiol-ene click chemistry [31,32], Bergman cyclization [33][34][35], Curtius rearrangement [36], Glasser-Hay coupling [37], nitrene-mediated C-alkylation (sulfonyl azide) [38], oxidative polymerization through pendant moieties [12], benzosulfone chemistry [39], carbodiimide coupling [40], benzoxazine chemistry [11], amide bond formation [10,31], cinnamoyl [40] and coumarin [2] photodimerization, guest-host interactions [41], hydrogen bonding [20,[42][43][44], and vulcanization [45].…”
Section: Introductionmentioning
confidence: 99%
“…A good example is the synthesis of well-defined statistical copolymers with protected functional groups as precursors of individual, unimolecular nanoparticles through intrachain crosslinking. Single-chain nanoparticles are emerging soft nanomaterials with promisingproperties for different end-use applications such as processing additives, [3] blend compatibilizers, [4] artificial enzymes, [5] photostable bio-imaging agents [6] and drug / siRNAdelivery systems, [7] among others. Different routes for the synthesis of single-chain nanoparticles with size below 20 nm have been progressively introduced relying either on covalent [8] or noncovalent [9] intrachain crosslinking.…”
mentioning
confidence: 99%